Investigation of Various Faults of 500 kV Transmission Line Design in Sarawak, Malaysia Using Power Systems Computer Aided Design - Yanuar Zulardiansyah, Arief; Hendri, Masdi; Nur Izziani, Roslan; Mohd Hafiez Izzwan, Saad; Hamzah, Eteruddin; Rosyid Ridlo, Al Hakim (2022)
This paper deals with a simulation investigation of an extra high voltage transmission line (500 kV) design in Sarawak, East Malaysia using Power Systems Computer Aided Design (PSCAD). Currently, the extra high voltage transmission system in Sarawak is mainly supplied by a 275 kV system covering the whole Sarawak region, starting from Miri district up to Kuching city - the so-called Sarawak Power Grid Backbone. Due to the rapid growth of industries and population in this state within the last ten years, improving the transmission system to become 500 kV is necessary. Therefore, the investigation of transient overvoltage and overcurrent in a new 500 kV transmission line system when faults occur due to various faults on the line and a lightning strike will be important to evaluate the system's reliability. The simulation results revealed that the lightning and three-phase faults cause the highest transient current surge in the transmission line. The highest lightning transient overvoltage was found at the receiving end of the transmission line.